KAMPANYE ‘YUK NABUNG SAHAM’ IDX UNTUK MENGUBAH MINDSET SAVING SOCIETY MENJADI INVESTING SOCIETY - Adiguna, Richad Saputra (Universitas Bina Sarana Informatika, 2018)
Abstract - One of the goals of communication is how to change the behavior, attitude and mindset of the individual or society. One of the efforts made is through campaigns. Campaigns are generally a form of persuasive communication aimed at changing attitudes, mindsets and behaviors of others as expected. The IDX's 'Yuk Nabung Saham' campaign aims to transform the people's mindset from saving society into an investing society. This campaign is a form of concern about the lack of literacy and the interest of the Indonesian people for investment. Investment is the main engine of the country's economic growth. Using descriptive qualitative approach, the researcher wanted to get descriptive data about campaign strategy used by IDX to change the society's mindset from saving society to investment society. The conclusion of the research on Yuk Nabung Saham's campaign strategy is this campaign is a structured and massive campaign. IDX makes use of all available media to educate the public about the benefits of investing. But of all activities just an effort to increase the number of investors, not specifically trying to build brand awareness products Yuk Nabung Saham.Â Keywords: Campaign, brand awareness, communication strategy, coomunication channel, stock